Factor income taxation, growth, and investment specific technological change - Monisankar Bishnu; Chetan Ghate; Pawan Gopalakrishnan (Indian Council for Research on International Economic Relations (ICRIER), 2013)
We construct a tractable endogenous growth model with production externalities in which the public capital stock augments investment specific technological change. We characterize the first best fiscal policy and show that there exist several labor and capital tax-subsidy combinations that decentralize the planner's growth rate. The optimal factor income tax mix is therefore indeterminate which gives the planner the flexibility to choose policy rules from a large set. Our model explains why many advanced economies experiencing similar growth rates have widely varying factor income tax rates.
Keywords: E2; E6; H2; O4; 330; Investment Specific Technological Change; Endogenous Growth; Factor Income Taxation; Welfare; First best fiscal policy; Indeterminacy; Endogenes Wachstumsmodell; Wirtschaftswachstum; Einkommensteuer; Optimale Besteuerung; Wohlfahrtsanalyse; Endogenes Wachstumsmodell